Performance of β-glucosidase immobilized on calcium alginate beads - Jameel, Ahmed Tariq; Yusof, Faridah; Johana, Syaira (2013)
Performance of immobilized β-glucosidase obtained from almonds (EC 3.2.1.21) on calcium alginate beads was studied by measuring the activity of the enzyme in terms of the generation of pnitrophenol from the hydrolysis of p-nitrophenyl-β-D-glucopyranoside (PNPG).The immobilized enzyme activity was compared with soluble enzyme and was found to decrease by 36.6% albeit with an increased operational stability in terms of easy recovery from the finished product, recurrent use and scale-up in various reactor configurations. The hydrolysis rate data exhibit Michaelis-Menten kinetics. The Michaelis constant were determined using Langmuir linearized plot which obtained vmax and Km as 20.88 μmol/mL.min and 0.0125 mol/L respectively. However, the immobilized β-Glucosidase did not show a sufficiently good operational stability on reuse.